Situation Report: Hungary, 10 February 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Prime Minister Spiljak Leaves Budapest Coverage of Czechoslovak Events The Results and Perspectives of Hungarian Foreign Trade Hungarian-Czechoslovak Economic Relations Implementation of Economic Reform in Consumer Cooperatives